Efektivitas Penggunaan Metode Hafalan Muraja'ah Terhadap Kemampuan Imla' Manqul di MTs Ponpes Cipari Garut - Sulaiman, Husnan; Ramdani, Dani (STAI Al-Musaddadiyah Garut, 2024)
Muslims have a duty towards the Qur'an to ensure its preservation on Earth from those who seek to destroy it. In addition, safeguarding the integrity of the Qur'an from potential threats or misuse involves perfecting its recitation (al-tilawah), writing (al-kitabah), and memorization (at-tahfidz), encompassing all its content in 30 parts. This effort ensures that the Qur'an remains preserved as a guide for Muslims indefinitely. One method to achieve this is through the Imla’ Manqul learning process, which is still implemented in both formal and informal educational institutions, such as at MTs Ponpes Cipari Garut. The objectives of this research are: (1) To describe the effectiveness of the Muraja'ah memorization method on the Imla’ Manqul skills of students at MTs Ponpes Cipari. (2) To evaluate the effectiveness of the Muraja’ah method on Imla’ Manqul skills and the accuracy of Qur'anic verse writing at MTs Ponpes Cipari. (3) To assess the students' perceptions at MTs Ponpes Cipari regarding the effectiveness of the Muraja'ah memorization method on their Imla’ Manqul skills. This study is a field research with a descriptive-analytical method employing a qualitative approach. Data sources include primary sources, such as books directly related to the research topic of the Muraja’ah memorization method and Imla’ Manqul learning, and secondary sources, including supporting books and texts related to the research. The results indicate a significant improvement in students' Imla’ Manqul abilities and Qur'anic verse writing skills through regular practice and the effectiveness of the Muraja’ah memorization method. The analysis involves perspectives from teachers and the school principal, highlighting the complexity of evaluating the effectiveness of the Muraja’ah method. The Muraja’ah memorization method has proven to provide a strong foundation for enhancing Imla’ Manqul skills and the accuracy of Qur'anic verse writing, and the positive perceptions of students affirm its profound impact on their Imla’ Manqul abilities, demonstrating the effectiveness of the Muraja’ah memorization method. Keywords: Muraja’ah, Imla’ Manqul, Learning Effectiveness